Impact of molar teeth distalization by clear aligners on temporomandibular joint: a three-dimensional study - Barakat Al-Tayar; Majedh A. A. Al-Somairi; Lina H. ALshoaibi; Xiaoli Wang; Junbin Wang; Jiajie Liu; Baher Al-Tayar; Xiaoli An; Qingzong Si (SpringerOpen, 2023)
Abstract Background Maxillary molar distalization is a common technique used in the non-extraction treatment of Angle Class II malocclusion that can effectively correct the molar relationship and create spaces for anterior teeth alignment. However, this approach may also impact the temporomandibular joint (TMJ) due to predictable changes in the posterior vertical dimension. Despite its widespread use, Class II malocclusions correction by molar distalization with clear aligners has not been investigated for their effects on the TMJ. Therefore, this study aimed to analyze the impact of sequential molar distalization using clear aligners on the TMJ. Methods Three-dimensional CBCT scans of 23 non-growing patients (7 males, 16 females; mean age 29.8 ± 4.6 years) with skeletal class I or II malocclusion and a bilateral molar class II relationship treated by sequential upper molars distalization with orthodontic clear aligners (Invisalign, Align Technology, San Josè, Ca, USA). A total of 46 joints were examined before and after molar distalization using Anatomage InvivoDental 6.0.3. Linear and angular measurements of the mandibular joint were measured, including joint parameters, inclination, position, and the dimension of the condyle and articular fossa. In addition, 3D volumetric spaces of the joint were analyzed. All data were statistically analyzed by paired T test to determine the differences between the pre-and post-orthodontic procedures. Results No statistically significant differences were found in all primary effects resulting from maxillary molars distalization by clear aligners on TMJ components measurements and joint spaces between T0 and T1. Meanwhile, statistically significant differences were observed in the linear position of the upper molars and the molar relationship parameter with at least P ≤ 0.05. Conclusion Treatment by sequential upper molars distalization with clear aligners does not lead to significant TMJ parameters changes in condyle and fossa spaces, dimensions, and positions.